2019
DOI: 10.3390/molecules24163008
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and Quantitative Evaluation of Heat-Induced Changes in Polyphenols and Antioxidant Capacity in Prunus domestica L. By-products

Abstract: Plum pomace, an agro-industrial waste product has received attention due to the worldwide popularity of plums. During convection, the content of flavan-3-ols decrease, except drying at 90 °C, whereas the content of i.e. chlorogenic, 3-p- and 4-p-coumaroylquinic acids, quercetin rutinoside, and galactoside was observed to increase along with the increase in process temperature. The highest content of all identified polyphenols was found in plum pomace powders obtained using a combination of convective at 90 °C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Previously, Liu, et al [ 8 ] demonstrated that peach peels have higher levels of antioxidant activities than peach flesh because of their higher phenolic content. Michalska, et al [ 21 ] found that the phenolic compounds in the pomace of plum are mainly procyanidin and catechin. Furthermore, different stone fruits contain different bioactive compounds; for example, the phenolic profile in plums and peaches varies greatly [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, Liu, et al [ 8 ] demonstrated that peach peels have higher levels of antioxidant activities than peach flesh because of their higher phenolic content. Michalska, et al [ 21 ] found that the phenolic compounds in the pomace of plum are mainly procyanidin and catechin. Furthermore, different stone fruits contain different bioactive compounds; for example, the phenolic profile in plums and peaches varies greatly [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fruit powders added to pellets (3%; w/w) were obtained from blackcurrant, chokeberry and cranberry spray-dried juice gained with addition of maltodextrin. The dominant groups of polyphenols in blackcurrant powders were: anthocyanins (cyanidin-and delphinidin-3-O-rutinoside being the most abundant), flavan-3-ols, flavonols and phenolic acids [33], whereas in chokeberry five major groups of polyphenolics were identified: phenolic acids, anthocyanins, flavonols, flavan-3-ols and procyanidins (UPLC analyses; data not shown). On the other hand, in cranberry juice powders the dominant groups were: flavonols, followed by anthocyanins, phenolic acids and flavan-3-ols (UPLC analyses; data not shown).…”
Section: Total Polyphenolsmentioning
confidence: 98%
“…This showed an influence of the processing type on the thermolability of polyphenols originated from fruit juice powders in snacks and proved their better retention after application of microwaves used for snacks preparation. It was indicated that the microwave vacuum drying process resulted in better retention of selected polyphenolic compounds during dehydration of plum products [33,34], thus, this method can be recommended for the preparation of products with improved functional properties. Previously, Camire et al [35] tested addition of commercial spray-dried powders into extruded corn breakfast cereals and it was observed that usage of selected types of fruit powders improved the total polyphenolics contents in products analysed and differed in terms of the chemical composition of fruits.…”
Section: Total Polyphenolsmentioning
confidence: 99%
“…Therefore, plums cannot be consumed fresh throughout the year, thus, the development of new dried powder products, obtained by drying industrial techniques, offers an alternative for the consumption at any season of the year. Plum powders can be obtained from whole fruit [3], plum by-products [4], or juices/concentrates [5]. Commonly used drying industrial processes include, apart from conventional air-drying, freeze-drying (FD), vacuum drying (VD), and spray drying (SPD) [6].…”
Section: Introductionmentioning
confidence: 99%